Aetiological process of idiopathic scoliosis: from a normal growing spine into a complex 3D spinal deformity. Issue 6 (December 2021) - Schlösser, Tom PC; Tsirikos, Athanasios I.; Castelein, René M.
Abstract: In more than a century of dedicated research into its aetio-pathogenesis, many attempts have been made to understand the exact cause of idiopathic scoliosis. In the literature, the number of causal theories is overwhelming and the aetiology of adolescent idiopathic scoliosis (AIS) is regarded as 'multi-factorial'. This overview focusses on recent studies that describe the changes from a normal spinal anatomy into the complex three-dimensional deformation and support the hypothesis that several paediatric deformities are a consequence of the unique way the human spine is biomechanically loaded. This has nothing to do with bipedalism, but with the way gravity and muscle tone translate to the unique sagittal shape of the spine, with its pelvic and lumbar lordosis, and the possibility to simultaneously extend the hips and knees. This leads to three rather than two forces acting continuously on the spine axial, anterior and posterior shear. An excess of anterior shear can result in spondylolisthesis and an excess of axial loading can cause osteochondrotic lesions. Unique for human are posterior shear forces, an excess of these result in decreased rotational stiffness of the involved vertebral segments. Certain sagittal spinal profiles, especially in girls around the pubertal growth spurt, predispose for development of a rotational deformity, as is idiopathic scoliosis. Once the growing spine decompensates into an idiopathic scoliosis, it will follow the right-sided rotational pattern that is already present in the non-scoliotic adolescent spine. The rotational deformation ultimately leads to rotatory lordosis around the apices of the curvatures and has major impact on lung function and quality of life.